PENGARUH KONSEP DIRI DAN LINGKUNGAN KELUARGA TERHADAP MINAT BERWIRAUSAHA MAHASISWA BARU - Anggreni, Ni Luh Putu Yesy; Cahayani, Ni Luh Putu (LP2M IKIP PGRI Bali, 2019)
Entrepreneurial interest is one's desire to start trying, create jobs according to their own will without coercion from others. Interest grows slowly in a person according to what is seen in his environment. The main goal of entrepreneurship is to create jobs for yourself, which will then have an impact on other job seekers. Growing interest requires a strong self-concept and a supportive family environment, especially in entrepreneurial activities. The tight competition in the world of work causes more unemployment in society. So to overcome this it is deemed necessary to foster interest in entrepreneurship. The study with the title